Resistance mechanisms and molecular epidemiology of Pseudomonas aeruginosa strains from patients with bronchiectasis. (22nd March 2022) - Cabrera, Roberto; Fernández-Barat, Laia; Vázquez, Nil; Alcaraz-Serrano, Victoria; Bueno-Freire, Leticia; Amaro, Rosanel; López-Aladid, Rubén; Oscanoa, Patricia; Muñoz, Laura; Vila, Jordi; Torres, Antoni
Abstract: Background: Non-cystic fibrosis bronchiectasis (BE) is a chronic structural lung condition that facilitates chronic colonization by different microorganisms and courses with recurrent respiratory infections and frequent exacerbations. One of the main pathogens involved in BE is Pseudomonas aeruginosa . Objectives: To determine the molecular mechanisms of resistance and the molecular epidemiology of P. aeruginosa strains isolated from patients with BE. Methods: A total of 43 strains of P. aeruginosa were isolated from the sputum of BE patients. Susceptibility to the following antimicrobials was analysed: ciprofloxacin, meropenem, imipenem, amikacin, tobramycin, aztreonam, piperacillin/tazobactam, ceftazidime, ceftazidime/avibactam, ceftolozane/tazobactam, cefepime and colistin. The resistance mechanisms present in each strain were assessed by PCR, sequencing and quantitative RT–PCR. Molecular epidemiology was determined by MLST. Phylogenetic analysis was carried out using the eBURST algorithm. Results: High levels of resistance to ciprofloxacin (44.19%) were found. Mutations in the gyrA, gyrB, parC and parE genes were detected in ciprofloxacin-resistant P. aeruginosa strains. The number of mutated QRDR genes was related to increased MIC. Different β-lactamases were detected: bla OXA50, bla GES-2, bla IMI-2 and bla GIM-1 . The aac(3)-Ia, aac(3)-Ic, aac(6″)-Ib and ant(2″)-Ia genes were associated with aminoglycoside-resistant strains. The gene expression analysis showed overproduction of the MexAB-OprM efflux system (46.5%) over the other efflux system. The most frequently detected clones were ST619, ST676, ST532 and ST109. Conclusions: Resistance to first-line antimicrobials recommended in BE guidelines could threaten the treatment of BE and the eradication of P. aeruginosa, contributing to chronic infection.